199k views
2 votes
Use substition to find the solution to the system of equations.

Use substition to find the solution to the system of equations.-example-1
User Nashcheez
by
5.0k points

1 Answer

3 votes

Answer:

C. (-3, -2)

Explanation:

Ok so since you are given the second equation with a variable by itself on one side of the equal sign, you can use substitution.

In the first equation, whenever you see a y, plug in x+1 instead of the y.

so: 5x + 7(x+1) = -29

Then you distribute the 7 to bother terms to simplify

5x + 7x + 7 = -29

Combine like terms next

12x + 7 = -29

Then, subtract 7 from both sides to get the 12x on its own

12x = -36

Then to get x by itself you divide by 12

x = -3

Now you have the x value, and you find the y value to complete the solution by plugging the x value into one of the given equations. I'll use the second because it is the simplest.

y = -3 + 1

y = -2

your solution is (-3, -2)

User Gwintrob
by
5.0k points